Through the prism of slavery : labor, capital, and world economy - Tomich, Dale W., 1946- (World social change., 2004)
"Tracing slavery's integral role in the formation of a capitalist world economy [Dale Tomich] reinterprets the development of the world economy through a 'prism of slavery'. Through a sustained critique of Marxism, world-systems theory, and new economic history, Tomich develops an original conceptual framework for answering theoretical and historical questions about the nexus between slavery and the world economy"--Page 4 of cover